Stabilization and Fiscal Empowerment : The Twin Challenges Facing India's States, Volume 1. Executive Summary and Main Report - World Bank (Washington, DC, 2014)
India, home to more than one billion people, has experienced rapid growth over the past decade, averaging about six percent per year between 1992/93 and 2003/04. The agenda backed in this report is one that receives widespread support from both the central and state governments in India. The fiscal stress of the late nineties gave rise to an intense state-level reform effort. Six years on, this report documents the many initiatives undertaken by the states to restore fiscal sustainability, and become more effective agents of development. It outlines successes, lessons learnt, and highlights further challenges, on both the expenditure side (chapter two) and the revenue side (chapter three). It also looks at the incentive framework within which the states operate (chapter four), and asks whether there is a feasible reform package that will take the states not only out of fiscal crisis, but strengthened to meet the development challenges which confront them. This chapter provides the context for what follows by outlining the role and increasingly divergent performance of the state governments (section two), and then in turn, the genesis of the fiscal crisis (section three), its developmental impact (section four), the reform response of the state and central governments (section five), and the reform challenges facing the states today (section six). Although associated with an increase in public spending, the fiscal crisis weakened the developmental and poverty impact of state governments, especially in the poorer states; it also called into question India's overall fiscal sustainability. This report is written to help share the lessons and success-stories to date, and to assist states and the central government in implementing the national agenda of state-level fiscal stabilization and empowerment. Given the low levels and the worrying recent trends in both the quantity of expenditure in priority expenditure areas, and the quality of expenditure across the board, there is an urgent need for expenditure restructuring to free up fiscal resources and for reforms to improve the quality of spending. Focus in this chapter on areas where expenditure can be cut rather than where it should be increased is not because we think there are no areas of underfunding. However, which particular areas should be increased, and by how much, will likely vary from state to state, depending on initial conditions, and identified priorities. The areas where savings can be made have much more in common across states, and so are the focuses of this report.